Association Between p53 Mutations with Tumoral Size and Dukes’ Stage Among Patients with Colorectal Carcinoma at The Hospital Central Fap, 1987-1996. - Rosas Marroquín, Nancy (1999)
OBJECTIVES: To determine the presence of p53 mutations among patients with colorectal carcinoma and their relationship with the tumoral size and with Dukes’ stage classification. MATERIALS AND METHODS: Anatomopathological specimens of 40 cases of colorectal carcinoma from the Hospital Central FAP, taken between 1987 and 1996, were re-examined. For detecting p53 protein mutations, the streptavidin-biotin immunoperoxidase immunohistochemical assay with do-7 antibody was used, pre-processing the samples with microwaves. RESULTS: All cases were adenocarcinomas, mostly moderately differentiated; 18 were in Dukes B, 16 Dukes in C, 4 in Dukes A and 2 in Dukes D stage. Tumoral size was directly related with Dukes’ stage, having a mean size of 5,5 cm3 for Dukes A, and 50,12 cm3 for Dukes D. There was a presence of p53 mutation in 55% of cases; the higher p53 expression, both the higher Dukes’ stage (a = 0,353) and the higher tumoral size (a = 0,376). CONCLUSION: Among our cases, p53 mutation accumulation was directly related with tumoral size and Dukes’ stage.